Pengaruh Motivasi, Prestasi dan Lingkungan Kerja terhadap Kinerja Karyawan - Susanti Susanti (JMK (Jurnal Manajemen dan Kewirausahaan), 2018)
This study aims to determine the factors that affect employee performance PT. Source Alfaria Trijaya Baron Nganjuk. These factors are Motivation, Preatation and Work Environment. Employees who have high work motivation will have a positive impact on the organization, so that organizational goals are achieved. The sample in this research is 20 employees. The variables used are Motivation, Preatation, Work Environment, and Employee Performance. Hypothesis testing is done by spreading the questionnaire / questionnaire as many as 20 employees Alfamart Baron Nganjuk. The questions used in the questionnaire are based on Likert scale. In this study using data analysis techniques Test Validity, Reliability Test, Multiple Linear Regression Analysis, Simultaneous Test (Test F), Persial Significance Test (Test t) with the help of computer program SPSS version 21.0. The results of this study show that partially and simultaneously Motivation, Preatation, and Work Environment affect Employee Performance.